“School of precariousness”: the production of consent to precarious work in administration internships (REGE Revista de Gestão, 2024)
Purpose: This study aims to understand the production of consent to precarious working conditions in administration students’ internship experiences. Study design/methodology: Thirteen students of an undergraduate program in Business Administration in a private university were interviewed. The students’ perceptions about the dynamics of the internship and their engagement in this experience were explored through thematic analysis. Findings: Internships became more than spaces to learn about the world of work. They are also locus of professional socialization toward precarious work. The detachment of internships from their educational scope is mediated by neo-normative control mechanisms that subjectively mobilize the interns, producing the institutionalization and appreciation of the precarious experience, re-signified as something that leads to autonomy, learning, and a job position. Practical implications: The article can help students, universities, and companies to assess the role of internships in training future professionals. Social implications: The research problematizes the internship as a form of professional socialization toward precarious work and its detachment from the original educational purpose. The article critically contributes to the debate about current professional socialization process of young students. Originality/value: The article highlights the subjective dimension that supports students’ consent to dysfunctional internships, discussing both the experience of work precariousness and exploitation, and the terms of the students’ engagement in such dynamics, bridging consent to neo-normative controls.